2006
DOI: 10.1074/jbc.m510603200
|View full text |Cite
|
Sign up to set email alerts
|

The Essential Vertebrate ABCE1 Protein Interacts with Eukaryotic Initiation Factors

Abstract: The ABCE1 gene is a member of the ATP-binding cassette (ABC) multigene family and is composed of two nucleotide binding domains and an N-terminal Fe-S binding domain. The ABCE1 gene encodes a protein originally identified for its inhibition of ribonuclease L, a nuclease induced by interferon in mammalian cells. The protein is also required for the assembly of the HIV and SIV gag polypeptides. However, ABCE1 is one of the most highly conserved proteins and is found in one or two copies in all characterized euka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
118
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(129 citation statements)
references
References 23 publications
11
118
0
Order By: Relevance
“…Therefore, ABCE1 protein is supposed to be the first role for eukarya development and in assembly of initiation complex during the translation process. The protein has adapted interaction with RNase L and Gag protein as a secondary function (7). In addition, ABCE1 protein has been suggested new important roles in translation termination and ribosome recycling in eukaryotes.…”
Section: Abce1 Protein Relates Closely With Eukaryotic Translationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, ABCE1 protein is supposed to be the first role for eukarya development and in assembly of initiation complex during the translation process. The protein has adapted interaction with RNase L and Gag protein as a secondary function (7). In addition, ABCE1 protein has been suggested new important roles in translation termination and ribosome recycling in eukaryotes.…”
Section: Abce1 Protein Relates Closely With Eukaryotic Translationmentioning
confidence: 99%
“…The protein was then demonstrated as a host factor essential for assembly of primate lentivirus capsids, especially for HIV-1 (5,6). Recent evidence indicated new important roles of ABCE1 protein in translation initiation, elongation, termination, and ribosome recycling in eukaryotes (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…ABCE1 has been shown to associate with 40S ribosomal subunits and initiation factors eIF2, eIF3, and eIF5, suggesting its role in pre-initiation complex assembly. [15][16][17][18] Consistently, ABCE1 depletion results in reduced polysome content and global translation in yeast, mammalian and Drosophila cells. 10,14,[16][17][18] ABCE1 is also involved in translation termination through interaction with release factors eRF1 and eRF3, occupying the GTPase center.…”
Section: Introductionmentioning
confidence: 68%
“…Studies in flies then showed that ABCE1 (known as Pixie in Drosophila) binds the 40S ribosome in an ATPdependent manner and depletion leads to an increase in in empty 80S ribosomes (Andersen and Leevers , 2007 ). ABCE1 interacts with the translation initiation factor eIF3 through the Hcr1 component in yeast (Dong et al , 2004 ), and with eIF2 and eIF5 in vertebrates (Chen et al , 2006 ). Hcr1 or eIF3 have additional functions, including also the coordination between termination and initiation, ribosomal subunit dissociation and rRNA maturation (Valasek et al , 2001 ), which made the functional interpretation of these interactions difficult.…”
Section: Abc Enzymes: Versatile Molecular Machines or Switchesmentioning
confidence: 99%
“…First insights into its core function emerged, when the Baillie, Dean, Hinnebusch, Leevers and Marygold labs found ABCE1 (Rli1p) to be involved in the assembly of the translation pre-initiation machinery, to interact with the translation initiation machinery and polysomes in yeast and to be important for translation and in worms, flies and vertebrates (Dong et al , 2004 ;Zhao et al , 2004 ;Coelho et al , 2005 ;Chen et al , 2006 ). At the same time, the Lill and Hurt labs found a functional link between the iron-sulfur clusters of ABCE1 and ribosome biogenesis (Kispal et al , 2005 ;Yarunin et al , 2005 ) while we could crystallize and determine the crystal structure of the twin ABC cassette of archaeal ABCE1 bound to ADP (Karcher et al , 2005 ) ( Figure 2).…”
Section: Abc Enzymes: Versatile Molecular Machines or Switchesmentioning
confidence: 99%